(untitled) (Journal of Advanced Veterinary and Animal Research, 2014)
The present study was carried out during the month of January 2014 when a total of 148 dogs with history of various diseases were presented to the Campus Veterinary Hospital, Teaching Veterinary Clinical Complex, College of Veterinary Science, Rajendranagar, Hyderabad, India. Out of 148 dogs that were presented to the hospital, 48 dogs had the clinical signs of loss of hair, itching, and reduced food intake. The dogs were restless and continuously rubbed their bodies against the walls in the houses, and scratching with their legs. Clinical examination of the dogs revealed presence of alopecia, pruritus, and the formation of small crusts. All 48 dogs were treated with ivermectin by subcutaneous injection dosed at 0.02 mL/kg body weight at a weekly interval for 2 to 3 weeks. All dogs were bathed with cypermethrin shampoo weekly once for 2-3 weeks. In the present study, it was observed that ivermectin/cypermethrin combination therapy was effective for the management of tick infestation in dogs. DOI: http://dx.doi.org/10.5455/javar.2014.a18 J. Adv. Vet. Anim. Res., 1(3): 145-147, September 2014